2020
DOI: 10.1155/2020/4969680
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of Concrete and Correlation with Microstructure Parameters Determined by 1H NMR

Abstract: Water and gas permeability coefficients of concrete with different water-binder (w/b) ratios and admixtures were measured by a self-designed test device based on the steady-state flow method for liquid and the method of differential pressure in stability for gas, respectively. In addition, the micropore structure of concrete was determined by 1H nuclear magnetic resonance (NMR). Results indicated that there are good correlations between water and gas permeability of concrete with different w/b ratios, with cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Not surprisingly, the diffusion rates are lower in the glass vials than the plastic vials, as the gas permeability of glass is lower than plastic, and also the walls of the plastic reactors are thinner than the glass walls. It may be possible to reduce diffusion further through a combination of thicker optode disks and changing the material chosen for the sealing O-rings (e.g., Viton), as the O-rings used in these tests are made of silicone, which typically has very high gas permeability [48]. Diffusion into the reactors is also generally easy to measure (as described in section 2.5.4), and consistent across replicates of each type of reactor.…”
Section: Plos Onementioning
confidence: 99%
“…Not surprisingly, the diffusion rates are lower in the glass vials than the plastic vials, as the gas permeability of glass is lower than plastic, and also the walls of the plastic reactors are thinner than the glass walls. It may be possible to reduce diffusion further through a combination of thicker optode disks and changing the material chosen for the sealing O-rings (e.g., Viton), as the O-rings used in these tests are made of silicone, which typically has very high gas permeability [48]. Diffusion into the reactors is also generally easy to measure (as described in section 2.5.4), and consistent across replicates of each type of reactor.…”
Section: Plos Onementioning
confidence: 99%
“…Not surprisingly, the diffusion rates are lower in the glass vials than the plastic vials, as the gas permeability of glass is lower than plastic, and also the walls of the plastic reactors are thinner than the glass walls. It may be possible to reduce diffusion further through a combination of thicker optode disks and changing the material chosen for the sealing O-rings (e.g., Viton), as the O-rings used in these tests are made of silicone, which typically has very high gas permeability [29]. Diffusion into the reactors is also generally easy to measure (as described in section 2.5.4), and consistent across replicates of each type of reactor.…”
Section: Diffusionmentioning
confidence: 99%
“…A true jack of all trades, the root barrier to ROL not only restricts radial diffusion of molecular O 2 but also diffusion of other gases and even movements of ions through the apoplast. The ROL barrier greatly restricts radial diffusion of H 2 (Peralta Ogorek et al ., 2021), even if molecular H 2 is a much smaller molecule compared to O 2 and, therefore, diffuses faster (Zhang & Cloud, 2006). Furthermore, radial diffusion of water is likewise restricted, sparking speculations that the ROL barrier is possibly of importance as a drought tolerance trait (Peralta Ogorek et al ., 2021), and it has been shown that low water potentials can induce a ROL barrier in roots of rice (Song et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%